Avaliação e seleção de híbridos de Megathyrsus maximus em relação a produtividade de forragem, valor nutritivo e tolerância ao estresse hídrico - Eduardo Moreira Barradas de Souza (2024)
The objective of this study was to evaluate and select genotypes of Megathyrsus maximus for forage productivity, nutritional value, and tolerance to water stress. CHAPTER II: This chapter aimed to evaluate and select improved hybrids of M. maximus with forage potential. The experiment, initiated in November 2020, was conducted under a randomized block design with three replications, arranged in split plots. The main plots consisted of eighteen improved hybrids and the control cultivars Mombaça and Massai, while the subplots corresponded to the seasons (rainy and dry). Productive and nutritional value characteristics were evaluated over two years (2021/2022). The FAI-BLUP selection index was used to identify hybrids that combined favorable characteristics in both the rainy and dry seasons. The FAI-BLUP index indicated the hybrids PM411, PM407, PM426, and PM412 for the rainy season, and the hybrids PM406, PM414, PM419, and the cultivar Mombaça for the dry season, demonstrating balanced and desirable genetic gains for all evaluated characteristics. CHAPTER III: This chapter aimed to evaluate the variability and response mechanisms of Megathyrsus maximus hybrids to water deficit and flooding. The experiment was conducted in a greenhouse under a randomized block design, in a factorial arrangement. The treatments consisted of a combination of eight genotypes of M. maximus, three water conditions (control, flooding, and water deficit), and two harvest times (1st harvest: after 20 days of water stress; 2nd harvest: 12 days after the recovery period). Productive and morphological characteristics were evaluated at the end of the stress period and after the recovery period. All hybrids subjected to water deficit showed a reduction in shoot and root mass. However, after the stress period, a survival response to water deficit was observed, with recovery of approximately 28.4% of the shoot and 16.3% of the root system in all genotypes. The hybrid PM409 stood out for its adaptation to flooding conditions, showing a higher root production (41.2%) compared to the average production of the other genotypes. Additionally, there was no reduction in leaf and stem mass production compared to the control condition. The results indicated that no genotype was tolerant to water deficit. On the other hand, the hybrid PM409 presented promising characteristics for tolerance to flooding stress.